A Graphical Proof of the Brouwer Fixed Point Theorem: N. Chuensupantharat, Poom Kumam, Sompong Dhompongsa - Team, Support (Thai Journal of Mathematics, 2017)
By simplifying the proof in [1], we give a new proof of the Brouwer fixed point theorem without using the Tietze (continuous) extension theorem.